STRATEGI BERSAING MEMODERASI INOVASI HIJAU, GROWTH OPTION DAN PUBLIC OWNERSHIP TERHADAP KINERJA KEBERLANJUTAN - Febriyanto, Muhammad Ikhsan; Nofryanti, Nofryanti; Rosini, Iin (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
Sustainability Performance Sustainability within a company in the form of reporting is an important step that can be taken towards corporate sustainability. Investors, regulators and other stakeholders are increasingly exploring their interest in developing sustainable reporting practices. The aim of this research is to analyze Competitive Strategies for Moderating Green Innovation, Growth Options and Public Ownership on Sustainability Performance in energy sector companies listed on the Indonesia Stock Exchange. This research uses secondary data from annual reports and sustainability reports. This type of research is associative quantitative. The sample selection in this research used a purposive sampling method, namely selecting samples based on predetermined criteria. The number of samples in this research was 28 companies. The research sample consisted of 140 observations made at energy sector companies during the 2018-2022 period. Hypothesis testing in this research is the model chosen, namely the Fixed Effect Model. The results of this research show that Green Innovation has a positive effect on Sustainability Performance. Growth Options have a positive effect on Sustainability Performance. Public Ownership has no effect on Sustainability Performance. Competitive Strategy moderates and strengthens the relationship between Green Innovation and Sustainability Performance. Competitive Strategy moderates and weakens the relationship between Growth Options and Sustainability Performance. Competitive Strategy moderates and strengthens the relationship between Public Ownership and Sustainability Performance.